Decomposition processes in coastal lagoons and their implications for the assessment of ecological health. Issue 3 (22nd January 2019) - Menéndez, Margarita; Abril, Meritxell; Colls, Miriam; Quintana, Xavier D.
Abstract: Aside from structural indicators, functional indicators have been suggested as a tool for assessing the health of transitional water ecosystems. The aim of this study was to assess the potential for the use of plant litter decomposition as a functional indicator of ecosystem health in coastal lagoons. A field experiment was conducted to assess the decomposition rate of Ruppia maritima enclosed in coarse and fine mesh litterbags and incubated in 10 Mediterranean coastal lagoons that conform to a gradient of ecological status produced by anthropogenic impacts as determined by a structural quality index. The microbial decomposition rate in fine mesh litterbags increased linearly along the ecological gradient. However, this relationship was not observed for the overall decomposition rate in coarse mesh bags. Decomposition rates in coarse mesh bags were negatively related to macroinvertebrate diversity, indicating that, in transitional habitats, such as coastal lagoons, high biodiversity is not a prerequisite for successful ecosystem functioning. The results suggest that functional indicators, such as the microbial litter decomposition process, should be used in addition to structural ones to detect anthropogenic‐derived environmental perturbations in coastal lagoons.